Structure and Magnetic Properties Of Fe/Si Nanoparticles Prepared by High Energy Milling Process - Muhammad Rifai; Yunasfi Yunasfi; Engkir Sukirman; Yosef Sarwanto; Mujamilah Mujamilah (Department of Physics, Sebelas Maret University, 2021)
The structure and magnetic properties of Fe/Si nanoparticle prepared by high energy milling process have been examined, focusing on the phase transition. Fe/Si nanoparticles were processed by high energy milling (HEM) for 10 hours to 50 hours with a weight per cent ratio of 9:1. Based on the X-ray diffraction (XRD) pattern, transmission electron microscope (TEM) observations, and vibrating sample magnetometer (VSM) analysis, the phase transition induced by HEM, were evidenced. The effect of structural state and the particle size on the magnetic properties such as magnetization was also studied. It was found that iron and iron oxides (-Fe2O3/ Fe3O4) phase were exhibited on all milled samples. The magnetization value of Fe/Si nanoparticles increased up to 20 hours with 142 emu/gr saturated magnetization and then decreased linearly with increasing milling time. Referring to the XRD result, this decline was initially caused by the iron oxide formation and magnetic interaction between iron and iron oxides nanoparticles. The phase and magnetic properties value changes related to the interaction mechanism between Fe atoms caused by interstitial occupied of Si atoms, particle size reduction, and oxidation process.